E-MAGAZINE TIME (EMT)-BASED DEVELOPMENT OF HISTORY LEARNING MEDIA IN THE PANDEMIC ERA - Muhjam Kamza; M Yusrizal; Ayu Noviana (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
The Corona Virus Disease (Covid-19) outbreak has changed the pattern of human activity, including the world of education. Face-to-face learning that is commonly used now must be replaced with online learning. This study aims to offer a new media in history learning, both in the scope of formal and non-formal education. The media in question is E-Magazine Time in digital form, containing all historical events that are arranged sequentially and briefly and fulfills the concept of space and time in a historical sense. E-Magazine Time is allegedly a new learning media that researchers are trying to offer to the world of education, especially learning that is carried out through electronic and online media. This study uses the Research and Development (R&D) method with the Decide, Design, Development, and Evaluation (DDD-E) model. The decision-making stage is trying to do field observations and literature studies. After that, they carried out the design stage to describe the learning content. Development is the process of making E-Magazine Time learning media using the Canva application with the help of Heyzine Flipbook. And the last stage is an evaluation which includes learning material experts, media experts, and students' rights to produce appropriate learning media. After passing the exam, the eligible E-Magazine Time is declared to be applicable in history learning for all levels of education, both in the realm of formal and non-formal education.